2019
DOI: 10.3390/rs11212579
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Phytovolume Estimation Methods Based on UAV-Photogrammetry and Multispectral Imagery in a Mediterranean Forest

Abstract: Management and control operations are crucial for preventing forest fires, especially in Mediterranean forest areas with dry climatic periods. One of them is prescribed fires, in which the biomass fuel present in the controlled plot area must be accurately estimated. The most used methods for estimating biomass are time-consuming and demand too much manpower. Unmanned aerial vehicles (UAVs) carrying multispectral sensors can be used to carry out accurate indirect measurements of terrain and vegetation morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…This study employed the Cloth Simulation Filter (CSF) from Zhang et al [44] in conjunction with a subsequent NDVI filter to classify ground points from which a DTM could be generated through interpolation. In Mediterranean shrublands, Carvajal-Ramirez et al [53] found the CSF performance was weaker relative to an NDVI classifier, and the authors called for the need to assess the impact of CSF parameter setting on ground-finding accuracy. In this study, CSF parameter optimization alone only marginally improved RMSE over the default parameters.…”
Section: Dtm and Chm Generation Capability Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study employed the Cloth Simulation Filter (CSF) from Zhang et al [44] in conjunction with a subsequent NDVI filter to classify ground points from which a DTM could be generated through interpolation. In Mediterranean shrublands, Carvajal-Ramirez et al [53] found the CSF performance was weaker relative to an NDVI classifier, and the authors called for the need to assess the impact of CSF parameter setting on ground-finding accuracy. In this study, CSF parameter optimization alone only marginally improved RMSE over the default parameters.…”
Section: Dtm and Chm Generation Capability Comparisonsmentioning
confidence: 99%
“…However, the addition of our NDVI threshold filter resulted in a large (>60%) improvement in RMSE. Drawing on the concept of the NDVI classifier from Carvajal-Ramirez et al [53], the combination of CSF with an NDVI filter leverages the strengths of both methods. The CSF identifies an initial set of ground points from which the NDVI filter removes misclassified vegetation.…”
Section: Dtm and Chm Generation Capability Comparisonsmentioning
confidence: 99%
“…The flights followed a simple grid. To address the potential issues of scale heterogeneity due to lowaltitude flights and steep terrain [35], and to obtain the most accurate information possible, the flight routes were planned using UgCS PRO software [36]. The flights were performed at an altitude of 30 m in the central hours of the day, when the sun's rays strike nearly perpendicular to the terrain, minimizing shadows that distort the spectral information.…”
Section: Drone Flights and Image Processingmentioning
confidence: 99%
“…Examples of unsupervised machine learning with UAV photogrammetry include analyzing photos of plants (more on object recognition after explaining NBV), agricultural models, and forestry management [63][64][65]. NBV appears in recent publications such as Bolourian and Hammad [66], Ashour et al [67], and Almadhoun et al [68].…”
Section: A Posteriori Informationmentioning
confidence: 99%